Collaborative Data Collection & Quality Analysis In Smart Phone Based Wireless Sensor Networks - et al., Wilson Thomas (International Journal of Advanced Science and Technology, 2019)
Collaborative sensing has become a novel approach for smart phone based data collection. Mobile Data Collection (MDC) is the use of mobile phones, tablets or PDAs for programming or data collection. MDC can be very useful to the evaluator who is collecting quantitative data for their evaluation or abstracting data for an evaluation. Other important issues we address in literature are issues relegated to energy, routing, security and bandwidth etc. This paper emphasizes the issues of data quality from the data aggregation or fusion process in wireless sensor network. The paper has presented a simple description of data, it’s essential characteristics, and has discussed some of the significant literature that discusses about enhancing the data quality as well as fault tolerant system in Smart phone based wireless sensor network. Finally, the paper briefs about the research gap that has been identified from the literature review.